If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+3=-5+4x+23
We move all terms to the left:
9x+3-(-5+4x+23)=0
We add all the numbers together, and all the variables
9x-(4x+18)+3=0
We get rid of parentheses
9x-4x-18+3=0
We add all the numbers together, and all the variables
5x-15=0
We move all terms containing x to the left, all other terms to the right
5x=15
x=15/5
x=3
| 4=3(v-12)-2 | | 180=19-2x | | -9d-17=16-6d | | -3x+4=-3+7 | | 6x-18=18-6x | | -15=5a+11-2a+6 | | 4(x-4)+x=14-3(x-6 | | -4(x+5)=(5)/(3)(3x-12) | | 8-5x+4=7x-1 | | -0.10(22)+0.65x=0.5(x-20) | | y/3-3/4=5y/6+1 | | -15-7j=-6j | | 6(w+3)=18 | | 6y-4(2-y)=12 | | -24m-8=-25-7 | | 6x-7x5=4x2+9 | | -7(4x-6)+5x=-142 | | m/4=9/6 | | x-7=-6+1/6x | | 9s=9+6s | | 4(2x-8)=-34+18 | | x-7=-601/6x | | –7+4w=13 | | x/9+8=19 | | -3y-1=20 | | -7x-x=-73.6 | | 8n+9=6n+5 | | 8=8x–4(x+8) | | 2(2x-9)=14 | | -1.29=-0.5(x-20/5) | | 92.3+40+x=180 | | 10-6c=-10 |